1995
DOI: 10.1179/joc.1995.7.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Ciprofloxacin with Metal Ions Contained in Antacid Drugs

Abstract: Simultaneous administration of antacids containing magnesium or aluminium and ciprofloxacin or other quinolones decreases the gastrointestinal absorption of those antibacterial agents. Current speculation about the mechanism of this interaction has focused on drug-cation chelation. The present study was designed to detect the protonation in solutions and the formation of the complex species at the pH levels typical of the gastrointestinal tract. It involves the study of ciprofloxacin in aqueous solutions conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Furthermore, aluminum ions contained in sucralfate as well as other cations substantially inhibit the antimicrobial activity of fluoroquinolones [15,[39][40][41]. Despite this drug interaction, the results of this study and a trial in volunteers [7] indicate that concomitant administration of sucralfate neither protects the endogenous intestinal flora, nor does it compromise the elimination of intestinal pathogens by i.v.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, aluminum ions contained in sucralfate as well as other cations substantially inhibit the antimicrobial activity of fluoroquinolones [15,[39][40][41]. Despite this drug interaction, the results of this study and a trial in volunteers [7] indicate that concomitant administration of sucralfate neither protects the endogenous intestinal flora, nor does it compromise the elimination of intestinal pathogens by i.v.…”
Section: Discussionmentioning
confidence: 76%
“…As the complexes probably form at a molar ratio of 1 : 1 to 3 : 1 (quinolones : cations) [50] and ciprofloxacin is only partially secreted into the intestinal lumen, a considerable excess of aluminum ions for binding of ciprofloxacin may therefore be expected. However, the aluminum ions dissociate from sucralfate mainly at low pH in the stomach [51], and ciprofloxacin is predominantly protonated at pH 1.5-3.5, which favors the formation of complexes [15]. Following intravenous administration, ciprofloxacin is mainly secreted in the jejunum and ileum [22,23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, we investigated the interaction of ciprofloxacin and moxifloxacin in the absence and presence of Mg 2؉ with whole bacteria and isolated lipopolysaccharide (LPS) from various rough mutant strains of Salmonella enterica chemotypes by applying different biophysical techniques. We found that the fluoroquinolones did not disturb the integrity of the OM and neither were incorporated into LPS monolayers nor displaced Ca 2؉ from LPS monolayers, suggesting that chelation of fluoroquinolones with divalent cations does not contribute to the antibacterial effect of fluoroquinolones.Fluoroquinolones have a tendency to chelate di-and trivalent cations (12,13,16,18,19,26,30,31,36). Therefore, it is tempting to speculate that fluoroquinolones chelate the magnesium that is associated with lipopolysaccharide (LPS) and maintains the integrity of the outer membrane (OM) (16).…”
mentioning
confidence: 99%
“…Fluoroquinolones have a tendency to chelate di-and trivalent cations (12,13,16,18,19,26,30,31,36). Therefore, it is tempting to speculate that fluoroquinolones chelate the magnesium that is associated with lipopolysaccharide (LPS) and maintains the integrity of the outer membrane (OM) (16).…”
mentioning
confidence: 99%